Viewpoint Computer Science Can Use More Science Software developers should use empirical methods to analyze their designs to predict how working systems will behave. - Morrison, Clayton T.; Snodgrass, Richard T. (Communications of the ACM, 2011)
The authors present their views on the importance of empirical scientific methods for software developers. They compare the LAMP ((Linux OS/Apache Internet server/MySQL DBMS/Perl PL) stack of computer code to the Saturn V rocket program developed by the U.S. National Aeronautics & Space Administration (NASA). The importance of debugging is noted, an argument is presented that general predictive models are needed, and some examples of computational models are provided.